Auctions for Oil and Gas Exploration Leases in India – An Empirical Analysis - Sen, A; Chakravarty, T (Oxford Institute for Energy Studies, 2013)
This paper addresses the following policy question: why, despite nearly 15 years of operation of India’s New Exploration Licensing Policy (NELP), representing two full exploration cycles has this regime yielded inconclusive results, both in terms of a firm indication of India’s resource potential, and increased domestic production? This paper argues that a substantial part of the reason for this lack of performance may lie in auctions and market design, and uses data for the period 1999–2010, covering nine rounds of auctions, to explore three lines of argument relating to some unintended consequences of the NELP. First, the regime has led to a highly concentrated market in upstream acreages where a small number of firms hold the largest amounts of acreage. Second, the regime has led to a ‘holdup’ problem that can be attributed to information asymmetries between the government and bidders, where winning bidders may later not fulfil their work programme commitments within the stipulated timeframe. Third, the lack of a clearer definition of the objectives of the auction and their relative importance, specifically, optimality versus efficiency, may have acted as a constraint on the effectiveness of the regime. We use a combination of theory and empirics to explore these three hypotheses. At the end of the paper we draw the results together, showing that problems relating to auctions and market design may have led to a cycle of information asymmetry and inefficiency, the net effect of which has been a slowdown in India’s domestic production, shortages in meeting supply targets, and the need for expensive imports. We suggest some policy options and areas for further research.